General Orders of the Board of Supervisors Providing Regulations for the Government of the City And County of San Francisco: Also, Ordinances of Park Commissioners (San Francisco: P.J. Thomas, 1884), 8. General Order no. 1,603—Relating to the Police Department, § 22—Prohibiting the Carrying of Concealed Deadly Weapons. Approved September 17, 1880 - (:unkn) unknown (General Publisher, 1880)
Prohibited the concealed carry of any pistol, dirk, or dangerous or deadly weapon.
--
Keywords: CARRY - CONCEALED